Follower’s Independent Critical Thinking and Job satisfaction : A systematic review using bibliometric methods - Ernawati, Fidyah; Hendrayanti, Silvia; Ardestya Linanjung, Yolanda (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Independent critical thinking and job satisfaction are two concepts which interrelated in the fellowership context. Followership is capacity and desire for doing behavior with the purpose for supporting leader and organization’s goals. Therefore, this research aims to analyze scientific literature which is publicated in independent critical thinking. Scopus database is used to collect literature about independent critical thinking based resulting search keyword and this research finishes 100 valid journals to more analyzis. And then, the researchers use VOS viewer to data visualization. The result showed that literature improvement about transformasional leader from 2000 until 2022. Some researchs have been done about transformational leader which involve collaboration of multi researcher.